Purified U7 snRNPs lack the Sm proteins D1 and D2 but contain Lsm10, a new 14 kDa Sm D1-like protein - Pillai, Ramesh S. (Oxford University Press, 2001)
U7 snRNPs were isolated from HeLa cells by biochemical fractionation, followed by affinity purification with a biotinylated oligonucleotide complementary to U7 snRNA. Purified U7 snRNPs lack the Sm proteins D1 and D2, but contain additional polypeptides of 14, 50 and 70 kDa. Microsequencing identified the 14 kDa polypeptide as a new Sm-like protein related to Sm D1 and D3. Like U7 snRNA, this protein, named Lsm10, is enriched in Cajal bodies of the cell nucleus. Its incorporation into U7 snRNPs is largely dictated by the special Sm binding site of U7 snRNA. This novel type of Sm complex, composed of both conventional Sm proteins and the Sm-like Lsm10, is most likely to be important for U7 snRNP function and subcellular localization.